CONCEPT OF VENTURE BUSINESS AND ITS PROSPECTS IN UZBEKISTAN - Saypullayev Ilhomjon Abduraxmonovich; Sidiqjonov Samandar Soxibjon o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article describes a general understanding of venture business, ideas and opinions about the prospects for the development of venture business in the Republic of Uzbekistan.